A SEMIOTICS ANALYSIS IN JAKARTA PUBLIC LIBRARY - Salma Afifah Jannah; Annisa Nur Khasanah; Sarah Syenta Mutiara Jingga (Cahaya Ilmu Bangsa Institute, 2024)
Semiotics, as the study of signs and meaning, is important in understanding how communication occurs in various aspects of life. One of the pioneers in this field is Ferdinand de Saussure, whose theory will be used in this research. This research uses a qualitative descriptive method. This research aims to analyze the signs in the Jakarta Cikini Library through the semiotic perspective of Ferdinand de Saussure. Specifically, this research focuses on the relationship between signifiers and signified in the library environment, including how these signs form meaning and guidance for visitors.